Severe injection site reactions after subcutaneous administration of Sayana®: a retrospective, post-marketing analysis of WHO and Swiss spontaneous pharmacovigilance reports (Swiss Medical Weekly, 2017)
PURPOSE Sayana® was introduced as the first depot medroxyprogesterone acetate-containing contraceptive that is administered via subcutaneous injection. Within 10 months, the Regional Pharmacovigilance Centre (RPVC) Zurich received several anonymous reports of serious local reactions after Sayana® administration. In this retrospective study, individual case safety reports (ICSRs) on local adverse drug reactions (ADRs) related to Sayana® were analysed from the WHO pharmacovigilance database. METHODS International, national and regional ICSRs during Sayana® administration up to 1 January 2016 were examined. Data on ADRs were retrieved from the WHO Global Database VigiBase™. Demographic data, drug administration information, duration of Sayana® treatment, latency time of the ADR, and its course, severity and outcomes were analysed. RESULTS Worldwide, 398 ICSRs after Sayana® use were registered in the database. We identified 20 reported terms that were potentially used to describe a persistent lipodystrophy. When only cases containing one or more of these 20 reported terms were selected, 323 (81.2%) international ICSRs remained for analysis. Of those, 91.6% (n = 296) were categorised as serious. The majority of the reactions (n = 193, 54.4%) did not recover. In the 67 Swiss ICSRs, 77 ADRs were reported using 10 different terms including severe or persistent local reactions like lipodystrophy, atrophy or fat necrosis. Thirty-two patients (47.7%) did not recover. All 11 regional cases reported to the RPVC Zurich were categorised as serious ADRs. For the majority of the patients (n = 7, 63.6%) the interval between the application of Sayana® and development of the lipodystrophy was between 2 and 4 months. Most of the reactions were irreversible (n = 9, 81.8%). One patient underwent plastic surgery for artificial infill of the dent. CONCLUSIONS Persistent local injection site reactions such as lipodystrophy, fat tissue necrosis or atrophy occur frequently after subcutaneous Sayana® use. These adverse drug reactions were recently integrated in the Swiss product information. Physicians and patients should be informed and advised about these potentially irreversible effects.